The importance of G2677T/A and C3435T polymorphisms of the MDR1 gene in the aetiology of colorectal cancer - Stańko, Grzegorz (Prz Gastroenterol, 2015)
INTRODUCTION: Colorectal cancer (CRC) is the most common cancer among patients, and its aetiology is still not precisely known. It is believed that 15–30% of colorectal cancers are genetically determined. P-glycoprotein (P-gp) encoded by the MDR1 gene in normal conditions plays an important role in the action of colon epithelial cells. However, the MDR1 polymorphism influences the P-gp expression and can weaken its effect against xenobiotics (procarcinogens) and increase the frequency of CRC. AIM: To evaluate the correlation between the MDR1 C3435T and G2677T/A polymorphisms and the risk of colorectal cancer. MATERIAL AND METHODS: The study group with colorectal cancer included 47 women and 60 men while the control group consisted of 110 healthy patients. The diagnosis in patients suffering from CRC was confirmed by histopathological report. Genetic analysis was performed using PCR-RFLP method. RESULTS: We showed only a correlation between the frequency of CT and TT genotypes of C3435T polymorphism and the risk of colorectal cancer in younger age. There was no correlation between the C3435T and G2677T/A polymorphisms of the MDR1 gene and other clinical parameters. CONCLUSIONS: Our findings suggest that T allele carriers of C3435T polymorphism have an increased risk of CRC. However, further studies are needed on a much larger number of patients and genes associated with metabolism and transport of xenobiotics including procarcinogens.